2007
DOI: 10.1097/01.prs.0000279475.99934.71
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Agarose Gel as a Dermal Filler: Histologic Evaluation of Subcutaneous Implants

Abstract: Agarose gel is a biocompatible product that can be considered for use as a tissue filler. Further investigation is required to assess its long-term efficacy and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 34 publications
0
51
0
3
Order By: Relevance
“…In our current system, the polysaccharide agarose provides structural support to the hydrogel system and is used to facilitate harvesting of formed beads from the emulsification vessel. Agarose has been shown to be well integrated with host tissue in a rat dermal model; agarose gel was degraded and newly formed collagen fibers were visible in the implants with no noticeable granuloma formation 32. The need for a structural filler (e.g., alginate) in the production of collagen beads has been also reported in other bead formulation protocols 33,34.…”
Section: Discussionmentioning
confidence: 82%
“…In our current system, the polysaccharide agarose provides structural support to the hydrogel system and is used to facilitate harvesting of formed beads from the emulsification vessel. Agarose has been shown to be well integrated with host tissue in a rat dermal model; agarose gel was degraded and newly formed collagen fibers were visible in the implants with no noticeable granuloma formation 32. The need for a structural filler (e.g., alginate) in the production of collagen beads has been also reported in other bead formulation protocols 33,34.…”
Section: Discussionmentioning
confidence: 82%
“…Agarose has been previously shown to be biocompatible in long-term studies, and so was chosen here to provide support to the collagen-filled channels. 15,47 The BNIs were reproducibly prepared by a casting device that accommodates an external MicroRenathane Ò tube (Braintree Scientific, Inc; OD 3 mm, ID 1.75 mm, and length of 12 mm) and manually perforated to increase nutrient and gas exchange (250 lm perforations, every 1 mm on all sides of the tube). A brush made of metal fibers (250 and 500 lm diameter) was inserted through the tube into a ''loading well''.…”
Section: The Biosynthetic Nerve Implantmentioning
confidence: 99%
“…In vivo studies have demonstrated that agarose provides a microenvironment that supports the non-hypertrophic and non-proliferative chondrogenic phenotype [55]. The physiological response to agarose resembles a wound-healing response similar to other biomaterials commonly used in the context of tissue repair [56]. Studies in both animals and humans have shown that agarose can be completely biodegraded and cleared after implantation without adverse effects [55, 57].…”
Section: Introductionmentioning
confidence: 99%